Das Bild von Herkus Monte in der deutschen und litauischen Literatur und Kultur: The image of Herkus Monte in German and Lituanian literature and culture - Kuzborska, Alina (Przegląd Wschodnioeuropejski, 2020)
This article focuses on the historical figure of the leader of the second uprising of the colonized Prussians against the Teutonic Order, Herkus Monte, who is presented here primarily as a literary figure. The increasing interest in Prussian history changed the written media, so that the order chronicle of the 13th century later turned into literary works, primarily historical novels and historical dramas in Germany. Because of the geographical proximity and linguistic relationship, the Lithuanians feel a strong affinity for the Prussians and their heroes. In the following, we analyze literary works by Lithuanian authors on the basis of which a feature film and an opera were created.